Loneliness as method: Henry James, individualism and the 'more intimate education'. Issue 2 (1st February 2020) - O'Sullivan, Michael
ABSTRACT: This article argues that James gives us a version of individualism through the aesthetic that ultimately relies on a privileged solitary regard for existence. What James describes in his own life as the 'essential loneliness of my life' is the 'essential ground' to his rendering of what he calls the 'inward life' and its 'more intimate education'. James still offers us today important lessons for education in an age that, as Michael D. Higgins argues, is devoted to individualism and competition. He grants the reader both private moments of 'dawdling' and a philosophy of artistic practice where the solitary reflection on beauty allows us to re-evaluate isolation and loneliness as entry points into the contemplation of the beautiful as a ground for education. It reminds us to allow students to come to terms with their loneliness as an emotion that grants them states of mindfulness and reflection that can then enable them to work out what are the reasons for their likes and dislikes.